Economic development : what everyone needs to know - Guigale, Marcelo M. (Oxford, United Kingdom : Oxford University Press, 2017)
The revised second edition of Economic Development: What Everyone Needs to Know® brings readers right into the trenches of development policies to show what practitioners are actually doing and explains the issues, dilemmas, options, frustrations and opportunities they face, day in and day out. In straightforward language and a question-and-answer format, Marcelo M. Giugale outlines the frontier of the development practice or, as he puts it, "...the point at which knowledge stops and ignorance begins." He takes readers from why it is so difficult to get governments to function, to the basic policies that economies need to work well, the powerful new tools for social assistance, and the challenges of inclusion, education, health, infrastructure, technology, data, and foreign aid. Giugale gives no definitive, universal answers. They don't really exist. Rather, he highlights what works, what doesn't, and what's promising. Drawing from examples across the world, his overall message is clear: economic development, and the poverty reduction that goes with it, have never been more possible for more countries.